ANALGESIC EFFICIENCY AND EFFECT ON MOTOR FUNCTION OF THE LOWER EXTREMITY OF BLOCK OF FEMORAL NERVE OR ADDUCTOR CANAL COMBINED WITH TIBIAL NERVE BLOCK AFTER TOTAL KNEE REPLACEMENT - D. V. Morozov; I. V. Boronina; A. A. Ryabtseva; T. A. Nikulina (Вестник анестезиологии и реаниматологии)
.